Ethyl 1-[2-(morpholin-4-yl)ethyl]-2-[4-(morpholin-4-yl)phenyl]-1H-1,3-benzimidazole-5-carboxylate - Yoon, Yeong Keng (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, C26H32N4O4, consists of two independent molecules. In both molecules, the ethoxy groups are each disordered over two sets of sites with occupancies of 0.695 (4):0.305 (4) and 0.877 (2):0.123 (2). The dihedral angles between the benzimidazole ring system and the adjacent benzene ring in the two molecules are 41.41 (5) and 31.46 (5)°. In the crystal, molecules are linked by C—H⋯O and C—H⋯N interactions.